Neighbors : Christians and Muslims building community - Womack, Deanna Ferree (Westminster John Knox Press, 2020)
"For a long time, American Christians have been hearing a story about Islam. It's a story about conflict and hostility, about foreigners and strangers. At the heart of this story is a fundamental incompatibility between the two religions going all the way back to their original encounters. According to that story, the only valid Christian response to Islam is resistance. But it's time to tell a different-and truer-story. Christians and Muslims have not always fought or lived in fear of each other. Christian communities in majority-Muslim countries have coexisted with their Muslim neighbors for centuries. More importantly, Muslims have been part of the American story from its beginning. And like their Christian neighbors, Muslims want to make the community in which they live a better place for all citizens. In Neighbors, Deanna Ferree Womack lays the groundwork for members of the two religions to understand, converse, and cooperate with each another. With models for cultivating empathy and interfaith awareness, Christians can move from neighborly intention to real dialogue and common action with Muslims in the United States"--